Can AI Enable Remote Surgical Assistance? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
The concept of a surgeon operating on a patient from miles away, once the realm of science fiction, is rapidly becoming a reality. The convergence of robotic...
Keywords: AI in Surgery and Robotics; Enable; Remote; Surgical; Artificial Intelligence; Healthcare